The Reciprocity at the Center: Economics and the Anthropocene from Xenophon's Economics - Helmer, Étienne (2025)
This article examines how Xenophon’s Economics makes reciprocity the key concept of just economic relationships between human beings and the Earth, and between human beings themselves in their exchanges. It invites us to reflect on an economic model that makes it possible to make this planet not a mere resource, but the place of a form of global justice.